Hidden mercy : AIDS, Catholics, and the untold stories of compassion in the face of fear - O'Loughlin, Michael J. (Writer in Washington, DC) (Broadleaf Books, 2021)
The height of the AIDS crisis in the United States in the 1980s and 1990s left many profound stories that remained untold. In Hidden Mercy, gay Catholic journalist Michael O'Loughlin uncovers the stories of Catholics who at great personal cost chose compassion. A compelling picture of those who responded to human suffering with mercy, offering insights for LGBTQ and other people of faith struggling to find a home in religious communities today.